New techniques for wound management: A systematic review of their role in the management of chronic wounds - Bekara, Farid (Arch Plast Surg, 2018)
Debridement is a crucial component of wound management. Recent technologies such as hydrosurgery (Versajet), ultrasound therapy (the MIST therapy device), or plasma-mediated bipolar radio-frequency ablation therapy (Coblation) seem to represent interesting alternatives for wound debridement. The purpose of this systematic review was to describe, evaluate, and compare these three recently developed methods for the management of chronic wounds. In January 2016, an electronic database search was conducted of MEDLINE, PubMed Central, and Embase for articles concerning these three innovative methods for the management of chronic wounds. A total of 389 references were identified by our search strategy, and 15 articles were included. We extracted data regarding the number and age of patients, indications, operating time, number of procedures, costs, wound healing time, decrease in exudation, perioperative blood loss, bacterial load, and the occurrence of complications. The 15 articles included studies that involved 563 patients who underwent hydrosurgery (7 studies), ultrasound therapy (6 studies), or Coblation (2 studies). Six randomized controlled trials were included that compared the use of a scalpel or curette to hydrosurgery (2 studies) or ultrasound therapy (6 studies). Hydrosurgery, in addition to being a very precise and selective tool, allows significantly faster debridement. Ultrasound therapy provides a significant reduction of exudation, and improves the wound healing time. No comparative study dedicated to Coblation was identified. Despite the obvious clinical interest of the topic, our review of the current literature revealed a lack of prospective randomized studies comparing these devices with each other or with standard techniques, particularly for Coblation and hydrosurgery.